2015
DOI: 10.1186/s13012-015-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

Gaps between research and public health priorities in low income countries: evidence from a systematic literature review focused on Cambodia

Abstract: BackgroundEvidence-based public health requires that research provides policymakers with reliable and accessible information reflecting the disease threats. We described the scientific production of research in Cambodia and assessed to what extent it provides appropriate insights and implications for practice to guide health policymakers and managers and knowledge relevant for translation.MethodsWe conducted a systematic review of scientific articles published on biomedical research in Cambodia. Regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
(29 reference statements)
0
32
1
1
Order By: Relevance
“…One interviewee further explained that mental health was another key priority in Cambodia, given the historical legacy of the genocide perpetuated in the 1970s; yet research and policy attention to mental health were said to be lacking due to dependence on donor agendas (see (Khan et al 2018) for more details). Similarly, a recent literature review found that few research reports on non-communicable diseases in Cambodia have been published, despite these accounting for the highest morbidity and mortality rates in the country (Goyet et al 2015).…”
Section: The Generation or Creation Of Policy Relevant Evidencementioning
confidence: 99%
“…One interviewee further explained that mental health was another key priority in Cambodia, given the historical legacy of the genocide perpetuated in the 1970s; yet research and policy attention to mental health were said to be lacking due to dependence on donor agendas (see (Khan et al 2018) for more details). Similarly, a recent literature review found that few research reports on non-communicable diseases in Cambodia have been published, despite these accounting for the highest morbidity and mortality rates in the country (Goyet et al 2015).…”
Section: The Generation or Creation Of Policy Relevant Evidencementioning
confidence: 99%
“…An analysis of the impact of the published research on evidence-based policy-making would also provide important insights, especially as a previous review has reported a relatively low level of actionable recommendations being made in the Cambodia health research literature. 12 In conclusion, it is well documented that the coordination and strategic planning of health sector rehabilitation and public health research is weak during periods of political transition and unprecedented aid inflow. 2 This analysis of HIV, TB, and malaria research activities during the past 15 years in Cambodia revealed that several important research areas may have been neglected; studies on TB and studies involving economic, qualitative, interventional, and genomics methods are underrepresented.…”
Section: Discussionmentioning
confidence: 98%
“…10 The distribution of donor aid to Cambodia may be influencing research conducted on TB, HIV, and malaria, as found elsewhere; 11 indeed evidence from the only systematic review to be conducted on health research in Cambodia -covering a number of conditions -indicates that there may be unequal representation of disease areas in terms of research publications. 12 The aims of this study were to compare TB research output with those for malaria and HIV and to analyse differences in research methods applied, in order to identify evidence gaps and future research needs.…”
Section: Introductionmentioning
confidence: 99%
“…The geographical affiliation of the author is seen to determine the nature and relevance of research, presenting 'local knowledge' tied to the communities and their needs (Connell 2018). Such knowledge is useful for generating 'actionable' inferences whether in health research (Goyet et al 2015) or climate science (Borland et al 2018). Framed in these arguments, there is some evidence to support a descriptively representative reading list, locally, on the basis of claims for substantive representation.…”
Section: Discussionmentioning
confidence: 99%